The effects of intranasal oxytocin on black participants’ responses to outgroup acceptance and rejection - Park, Jiyoung; Woolley, Joshua; Mendes, Wendy Berry (Frontiers in Psychology, 2022)
Social rejection is assumed to have widespread negative effects on the recipient; however, within interracial interactions social rejection can be attributionally ambiguous. Rejection might be due to personal characteristics or social identity membership. Here, we examined the role that oxytocin—a neuropeptide putatively linked to social processes—plays in modulating reactions to rejection or acceptance during interracial interactions. Black participants (N = 103) received intranasal oxytocin or placebo and interacted with a White, same-sex stranger who provided negative or positive social feedback. Following negative feedback, oxytocin reduced anger suppression. After positive feedback, participants given oxytocin (vs. placebo) tended to display approach-oriented cardiovascular responses of challenge (vs. threat), exhibited more cooperative behavior, and perceived the partner to have more favorable attitudes toward them after the interaction. Although oxytocin did not modulate testosterone reactivity directly, our exploratory analysis showed that the less participants suppressed anger during the interaction with their partner, the greater testosterone reactivity they displayed after the interaction. These results survived the correction for multiple testing with a false discovery rate (FDR) of 20%. Discussion centers on the interplay between oxytocin and social context in shaping interracial interactions.